Multi-Scale Model Updating for the Mechanical Properties of Cross-Laminated Timber - Saavedra-Flores, E (Elsevier Ltd, 2016)
In this paper we propose a homogenisation-based four-scale model for the mechanical properties of cross-laminated timber. The spatial scales considered in this study are the wood cell-wall, the wood fibres, growth rings and the structural scale. The computational homogenisation scheme is solved sequently from the lowest to the highest level in order to determine the effective mechanical properties of each material scale. As we are interested in improving the predictions of our computational simulations, we propose an optimisation strategy to calibrate the micro-mechanical parameters. Our numerical predictions are compared with experimental results and are validated successfully. © 2016 Elsevier Ltd